ORGANIZATIONAL AND ECONOMIC POTENTIAL OF RE-ENGINEERING BUSINESS PROCESSES IN THE CONTEXT OF MARKETING ACTIVITY OF AN INDUSTRIAL ENTERPRISE TO ENSURE ITS EFFICIENT INNOVATIVE ACTIVITY - Denys Kobyzskyi (Сучасний стан наукових досліджень та технологій в промисловості, 2018)
The subject matter of the study is the principle of organization of innovative activity of domestic industrial enterprises and functional links between marketing and innovation activities in the process of re-engineering business processes. The goal of the article is to reveal the organizational and economic potential for attracting business process re-engineering in the marketing activities of industrial enterprises to ensure efficient innovative marketing in particular and effective innovative activity in general. The following tasks were solved in the article: statistical indicators of innovative activity of domestic industrial enterprises and corresponding sources of financing were investigated; scientific works on the topic of innovative marketing, innovation marketing, the innovative component of re-engineering and re-engineering of business processes in marketing activities were studied and analyzed. The following methods were used: the comparative analysis, system approach, statistical analysis.  The following results were obtained. Ukrainian industrial enterprises lack innovations. Enterprises should independently find out how to ensure efficient innovations using the available resource potential. Innovations is a clearly defined benchmark for the industry and moreover, innovations should take place not only in technologies and the final product but also in management. All these factors require involving radical innovations which include the re-engineering of business processes. In the period of crucial changes in both internal and external business environment, marketing should become responsible for adapting the enterprise to new principles of operation. Thus, a number of activities in the area of marketing and innovation were listed, the innovative function of marketing of industrial enterprises was specified and the theoretical and methodical approach to the innovative marketing of industrial enterprises in the process of re-engineering business processes was upgraded. Conclusions. Re-engineering business processes in the context of industrial enterprise marketing include a significant organizational and economic potential that can be used to ensure the efficient innovative marketing in particular and the efficient innovative activity in general.